2021
DOI: 10.1007/s10347-021-00624-1
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentology and distribution of late quaternary calciturbidites and calcidebrites in the Mozambique Channel (Southwest Indian Ocean)

Abstract: Submarine gravity flow processes on carbonate platform slopes can lead to the deposition of calciturbidite and calcidebrite beds on the adjacent deep-water seafloor. Such deposits have been previously found to occur more frequently during sea-level highstands, leading to increased export of carbonates to the deep sea during interglacial periods. Here, we document a new occurrence of these types of event beds in cores near a series of volcano-cored carbonate platforms in the Mozambique Channel (SW Indian Ocean)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…Sediment core lithology around submarine canyon mouths of the southern Ryukyu forearc varies depending on the connectivity of submarine canyon heads with coral reefs. In pure carbonate and mixed carbonate-siliciclastic settings, sediment exports from shallow carbonate platforms and reefs to the deep-sea is controlled by the carbonate and clastic sediment productivity, type of canyon, and connectivity of shelf channel with the submarine canyon (Mullins, 1983;Eberli, 1991;Jorry et al, 2010Jorry et al, , 2020Puga-Bernabéu et al, 2011, 2014Counts et al, 2018Counts et al, , 2021. First, we will examine the relationship between sediment core lithology and the type and connectivity of submarine canyons.…”
Section: Connectivity Of Submarine Canyon Heads With Coral Reefs and ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Sediment core lithology around submarine canyon mouths of the southern Ryukyu forearc varies depending on the connectivity of submarine canyon heads with coral reefs. In pure carbonate and mixed carbonate-siliciclastic settings, sediment exports from shallow carbonate platforms and reefs to the deep-sea is controlled by the carbonate and clastic sediment productivity, type of canyon, and connectivity of shelf channel with the submarine canyon (Mullins, 1983;Eberli, 1991;Jorry et al, 2010Jorry et al, , 2020Puga-Bernabéu et al, 2011, 2014Counts et al, 2018Counts et al, , 2021. First, we will examine the relationship between sediment core lithology and the type and connectivity of submarine canyons.…”
Section: Connectivity Of Submarine Canyon Heads With Coral Reefs and ...mentioning
confidence: 99%
“…Carbonate production on carbonate platform tops and sediment exports from platforms to surrounding deep seas by plumes and gravity flows have been influenced by late Quaternary large scale oscillations of sea level (e.g., Mullins 1983;Droxler and Schlager, 1985;Eberli, 1991;Jorry et al, 2010Jorry et al, , 2020Webster et al, 2012;Counts et al, 2021). In many studies, a general correlation has been found between an increase in calciturbidite frequency and periods of sea-level highstand (Droxler and Schlager, 1985;Jorry et al, 2010Jorry et al, , 2020Webster et al, 2012;Wunsch et al, 2017;Counts et al, 2018Counts et al, , 2021. However, the exact occurrence patterns of calciturbidites are variables, reflecting the bank-top water depths (the timing of the flooding of bank-top), type of submarine canyon, and shelf-edge morphology (Jorry et al, 2010;Puga-Bernabéu et al, 2014).…”
Section: Temporal Change In the Frequency Of Calciturbiditesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sediment distribution patterns on the shelf slopes and within slope channels demonstrate that the sediment composition of (non‐)skeletal grains present in these environments not only links to the depositional setting itself but also has strong ties to the shallow‐water distribution patterns of the (non‐)skeletal sediments as demonstrated for the Gulf of Aqaba/Eilat (Perl, 1997), but also for numerous carbonate‐dominated environments (e.g. Haak & Schlager, 1989; Reijmer et al ., 1992, 2012, 2015; Jorry et al ., 2020; Counts et al ., 2021). Hence, the statement of Ash‐Mor et al .…”
Section: Gravity Deposits In Clastic and Carbonate Dominated Settingsmentioning
confidence: 99%
“…study (2017, section 4.3, last paragraph), the quantity and size of the transported LBF in the individual gravity flows is discussed as an expression of the magnitude of an earthquake. This LBF quantity to earthquake link fully disagrees with what is known from comparable variations in LBF occurrences in carbonate gravity flows – MTDs portrayed for a wide range of tectonic stable depositional environments, for example: (i) general (Spence & Tucker, 1997; Reijmer et al ., 2015); (ii) Bahamas (Crevello & Schlager, 1980; Principaud et al ., 2015; Tournadour et al ., 2015; Wunsch et al ., 2017, 2018; Le Goff et al ., 2020); (iii) Great Barrier Reef (Webster et al ., 2016); and (iv) Mozambique Channel (Counts et al ., 2021). The occurrence of certain LBF in gravity flows – MTDs merely links to a specific location or an assembly of locations within the margin to slope domain from which the sediment‐mass originated in response to destabilization processes.…”
Section: Lbf Quantity and Earthquakesmentioning
confidence: 99%